2009
DOI: 10.1016/j.visres.2009.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Focal activation of the feline retina via a suprachoroidal electrode array

Abstract: This paper presents the results of the first investigations into the use of bipolar electrical stimulation of the retina with a suprachoroidal vision prosthesis, and the effects of different electrode configurations on localization of responses on the primary visual cortex. Cats were implanted with electrodes in the suprachoroidal space, and electrically evoked potentials were recorded on the visual cortex. Responses were elicited to bipolar and monopolar stimuli, with each stimulating electrode coupled with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
109
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 41 publications
14
109
4
1
Order By: Relevance
“…35 In vivo and in vitro studies have lent support to this hypothesis, 31,36 wherein an increase in hexapolar activation threshold is observed to be up to three times that of monopolar.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…35 In vivo and in vitro studies have lent support to this hypothesis, 31,36 wherein an increase in hexapolar activation threshold is observed to be up to three times that of monopolar.…”
Section: Resultsmentioning
confidence: 91%
“…This proved effective at charge containment and confirmed findings from studies in auditory prosthetics have shown that using different return path configurations can result in greater spatial selectivity. [31][32][33][34] Thus, this strategy also may be beneficial for retinal implants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulations were applied at 250 µA with 200 µs phase widths, which correlated with the charge injection threshold required to measure an evoked response in the visual cortex in previous in vivo experiments. (11,17) Electrodes were placed in an incubator at 37°C and 100% humidity, and the maximum voltage excursion across two electrode interfaces (bipolar stimulation) was measured daily for 50 days. Stimulation was constant at 250 Hz and the medium was replaced every 2 days to preserve the activity of the proteins.…”
Section: Stabilitymentioning
confidence: 99%
“…Additionally, stimulation of vision using a more distant placement of devices, such as suprachoroidal and sclera placements, have been shown to require a higher charge injection per phase in animal models. (12,17) It is clear that sufficient stimulation for useful vision across a wide range of patients will require a careful balance between electrode size and the charge injection capacity of the chosen material. While coating technologies show considerable promise in improving safe charge injection, PEDOT is not yet approved by regulatory bodies, and activated IrOx for vision prostheses is still under efficacy testing.…”
Section: Introductionmentioning
confidence: 99%